Constraints Of Community Participation On Domestic Solid Waste Management In Sodo City, Wolayita Ethiopia - Meja, Merihun Fikru; Ayano, Nigatu Bushura (Archives of Business Research, 2021)
This study was undertaken to assess the constraints of community participation on domestic solid waste management activities in sodo city, Ethiopia. Both qualitative and quantitative data were collected from primary and secondary sources. The primary data were collected from 204 households who were randomly selected from four kebeles (Fana, Gebeya, Gido and Selame) of wolayita-sodo city. The primary data were gathered through survey questionnaire, key informant interview, focus group discussion, and field observation. The secondary data were collected from central statistics authority, city municipality, published and unpublished sources. The collected data were analyzed by using descriptive statistics and binary logistic regression model. The result shows that participation of communities on domestic solid waste management was low. The result from binary logistic regression model revealed that the probability of household participation on domestic solid waste management was positively and significantly constrained by educational level of households, household income, and household access to main road, small-scale enterprise service coverage and supply of waste facility. On the other hand, sex of household head and marital statuses were negatively and significantly constrained the probability of household participations on domestic solid waste management. As a result, widening the horizon of education and training, expanding small-scale enterprise service coverage, supply of waste facility and provision of road infrastructure within the community was suggested to reduce constraints of community participation on domestic solid waste management.